Implementasi Program Bantuan Operasional Sekolah di Sekolah Mengah Pertama Negeri 3 Semarang - Marpaung, Sherli Marintan; Hidayat, Zainal (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
Education is one of the most important aspect in human lives that helps making and improving a better life as a nation. Education is also a way to prepared students for their role in the future through guidance, teaching and training. The government has he main role in fulfilling the needs of education in society. The government has made a policy in educational field that is School Operational Assistance program. School Operational Assistance program has made to support 9- year compulsory education program. The government provides funds to schools so that students are exempt from all tuition fees. This program was started in July 2005 along with the beginning of 2005/2006 academic year. This research was conducted in SMP N 3 Semarang which is one of the best school in Semarang. This research is based on the reality of the implementation that there are several problems such as the limited use of School Operational assistance funds for schools as implementers. Based on the research, the implementation of School Operational Assistance program in SMP N 3 Semarang is still not optimal. Therefore the recommendation is by not limiting the use of School Operational Assistance funds for every schools, funding school based on the needs of each schools, and understanding the use of School Operational Assistance funds to avoid misperception in the implementation